Digital Marketing and Electronic Word of Mouth: A Literature Review - Mohammad Hamim Sultoni (Manajemen Bisnis, 2023)
This research using literature study as a methods. In addition to variables, a method often used in digital marketing research is to use quantitative methods with the Structural Equation Modeling (SEM) approach. The results showed that the variables that are consist of several variable, there are quality of the website that have the function to measure the reliability of the site, the quality of the information provided by the site, and the desire of consumers to share their experience of using it to the other consumers (E- WOM).